A class of linear and nonlinear Fredholm integral equations of the third kind - Avyt Asanov; Kalyskan Matanova; Ruhidin Asanov (Kuwait Journal of Science)
In this paper we are applying a new approach to prove the uniqueness and existence theorems for linear and nonlinear Fredholm integral equations of the third kind.